Channel width adaptation algorithm in multi-channel vehicular networks - PENG Xin; LI Ren-fa; LIU Liang-jiao (Tongxin xuebao)
Aiming at the low utilization of spectrum resource in vehicular networks,an algorithm base on semidefinite programming was presented,which could be utilized to channel width adaptation of multi-channel vehicular networks.Firstly,the algorithm need to measure the distance with the surrounding vehicles to compute conflict graph.And then the semidefinite programming relaxation was employed to coordinate the competition of spectrum resource.Finally,the ultimate channel width adaptation was computed based on the initial channel assignment and compression process.Simulation results demonstrated that the new algorithm not only can promote network throughput,but also perform well on extremely dynamic topology.